Traditional knowledge of basketry practices in a Northeastern Region of Portugal - Carvalho, Ana Maria (2008)
This poste r presents and discusses the local basketry knowledge and weaving skills of both men and women from 25 rural villages of Braganca, a region in the northeast of Portugal. The information was collected through 60 semi-structured interviews and partkipant observation. Pictures were taken to document the entire weaving process; a collection of artefacts was also established. Data on 30 plants used in the manufacture of baskets or other items were recorded and analysed quantitatively in order to establish the importance of each corresponding species. The collected data shows a high number of species, local traditional practices and different uses related with basketry. Special attention is given to cultural and gender values associated with basketry in that particular region and to the processes of both knowledge 1055 and transmission